Self-management training program by using cognitive technique (a quasi experiment on the students of UPI Kampus Serang) - Chudari, Ima (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2017)
The goal of this study is to construct an effective program which can improve students’ self-management of UPI Kampus Serang by using cognitive technique. The starting point of this study is began at the revealed undisciplined students behaviors such as tardiness in attending classes, tardiness in submission of assignments, unable to use their free-time effectively and productively and the others disorderly behaviors. Cognitive technique hopefully brings a self management which effectively changes the inadequate idea in the mind and bad feeling in the heart into an acceptable quality of this mental and behavior. Also, this technique hopefully emerges a basic change in the procedure of self management. Research design applies the Latin Square technique which is derived from one of Within Subject technique (Heppner, Wampold, Kivlighan, 2008). In this study, population of students was trained in their self management (SM) skill. The aspects of SM skill which are trained to the students namely time management (TM), social skill (SS), and self-directed learning (SDL). The training of these three SM skills applied three different cognitive technique that are planning (P), problem solving (PS) and self-instruction (SI). Thus students formerly divided into three groups of population to give treatment to each of the SM aspects (TM, SS, SDL) for each group by applying the three different cognitive aspects (P, PS, SI). The final outcome of this study shows that there are no significance different results in the applying of those three cognitive techniques in order to improve the students’ SM skills. Nevertheless, this training program has empirically proven that the program is able to improve the SM skills of the students at the rate of 30% better than before. Then, the final product of this study is a program of students Self Management Training by using Cognitive Technique.